9000 = -6t^2 + 3t +10000
t= seconds
H= meters
Solve for t
t= seconds
H= meters
Solve for t
-
9000 = -6t² + 3t +10000
9000+6t² -3t -10000=0
6t² -3t-1000=0
put it in a quadratic form ax² +bx+c=0 i.e.
6t²+( -3)t+(-1000)=0 where a=6 b=-3 c=-1000
use these values in the formula
x=(-b+root under(b² -4ac))/2a and x=(-b-root under(b² -4ac))/2a to solve x.
9000+6t² -3t -10000=0
6t² -3t-1000=0
put it in a quadratic form ax² +bx+c=0 i.e.
6t²+( -3)t+(-1000)=0 where a=6 b=-3 c=-1000
use these values in the formula
x=(-b+root under(b² -4ac))/2a and x=(-b-root under(b² -4ac))/2a to solve x.